New troglobitic species of Xangoniscus (Isopoda: Styloniscidae) from Brazil, with notes on their habitats and threats - Cardoso, Giovanna Monticelli; Bastos-Pereira, Rafaela; Souza, Leila Aparecida; Ferreira, Rodrigo Lopes (Zootaxa, 2020)
In the present work, five new species of Xangoniscus are described, increasing to eight the number of the known troglobitic species for the genus. Xangoniscus species can be distinguished from each other by the shape of pleonites epimera, the number and size of aesthetascs in the distal article of antennula, the modifications on pereopods, the shape of male pleopods and the proportion between uropod rami. Species from this genus are known for the states of Minas Gerais and Bahia with Xangoniscus aganju representing the northernmost occurrence, and X. lundi n. sp. and X. dagua n. sp. the southernmost occurrences. Of the six caves where specimens were collected, four are not registered in the national speleological database, what points to all the potential to yet be discovered regarding number of cavities and the associated biodiversity in Brazil. Some of the here mentioned type localities are not located inside protected areas, therefore exposing the species to risks related to the adjacent land use and consequent influence on water table level and input of food resources. The contribution of this work with descriptions of new troglobitic species provides support to consider them as plausible candidates to be assessed in the next list of threatened species as well as to elaborate conservation actions for the species, the caves where they inhabit and the surrounding landscape.